2012
DOI: 10.1021/ja3057002
|View full text |Cite
|
Sign up to set email alerts
|

Studies toward the Unique Pederin Family Member Psymberin: Structure–Activity Relationships, Biochemical Studies, and Genetics Identify the Mode-of-Action of Psymberin

Abstract: Psymberin is the only member of the pederin natural product family that contains a dihydroisocoumarin side chain. Structural modifications of psymberin uncoupled inhibition of protein translation from cytotoxicity, suggesting that psymberin has more than one bioactivity. A forward genetic screen in Caenorhabditis elegans was conducted to identify the molecular target(s) of psymberin. Multiple independent psymberin-resistant mutants were isolated, each containing the same point mutation in a gene encoding a rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
2
34
0
3
Order By: Relevance
“…8,9) Additionally, genetic studies with Caenorhabditis elegans show that irciniastatin A primarily targets the ribosome. 10) Cell-surface tumor necrosis factor (TNF) receptor 1 is processed into its soluble form by TNF-α-converting enzyme (TACE), also referred to as a disintegrin and metalloproteinase 17. 11) We have previously shown that three translation inhibitors, i.e., acetoxycycloheximide, cytotrienin A and deoxynivalenol, rapidly induced the ectodomain shedding of TNF receptor 1 in human lung carcinoma A549 cells.…”
mentioning
confidence: 99%
“…8,9) Additionally, genetic studies with Caenorhabditis elegans show that irciniastatin A primarily targets the ribosome. 10) Cell-surface tumor necrosis factor (TNF) receptor 1 is processed into its soluble form by TNF-α-converting enzyme (TACE), also referred to as a disintegrin and metalloproteinase 17. 11) We have previously shown that three translation inhibitors, i.e., acetoxycycloheximide, cytotrienin A and deoxynivalenol, rapidly induced the ectodomain shedding of TNF receptor 1 in human lung carcinoma A549 cells.…”
mentioning
confidence: 99%
“…Here, we describe the synthesis of psymberin analogs that were useful for the structure-function and mode-of-action studies that will be detailed in a subsequent article. 13 The terminal olefin of 1 is distinct from the exocyclic double bond present in other pederin family members. In the subsequent article, we demonstrate that the homoallylic ether in pederin is responsible for the irritant/blistering activity associated with this class of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent article, we detail our biological investigations that led to the target identification of psymberin, and attributes that distinguish it from the pederin/mycalamide family of natural products. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Representative examples of these compounds have been synthesized by considerable numbers of organic chemists in the last 10 plus years. The following papers should be consulted by readers interested in the synthetic processes used (Jewett and Rawal, 2007; Jiang et al, 2007; Nishii et al, 2009; Wan et al, 2011; Wu et al, 2011, 2012; Mosey and Floreancig, 2012; Floreancig, 2014; Uesugi et al, 2015). Of these, the review by Mosey and Floreancig (2012) gives a relatively thorough overview of the isolation, biological activities, and medicinal chemistry of these agents.…”
Section: Marine Metabolites Based Upon a Terrestrial Beetle Toxinmentioning
confidence: 99%